ANALISIS PROSES PEMODELAN MATEMATIS MAHASISWA DITINJAU DARI LEVEL KEMAMPUAN PENALARAN PADA MATERI FUNGSI KONSUMSI DAN TABUNGAN - Desmiani Susanti (As-Sulthan Journal of Education, 2026)
This study aims to analyze students' mathematical modeling processes based on their levels ofmathematical reasoning ability. The study employed a qualitative descriptive approach with a casestudy design involving six undergraduate students from the Mathematics Education Program,selected through purposive sampling. The participants consisted of two students from eachreasoning level (low, medium, and high). Data were collected through a written mathematicalmodeling task and think-aloud interviews and analyzed using the Blum and Leiß mathematicalmodeling cycle. The findings indicate that students with high mathematical reasoning successfullycompleted all stages of the modeling process in a systematic manner, demonstrating creativereasoning and accurate interpretation. Students with medium reasoning reached the interpretationstage but still experienced difficulties distinguishing between the concepts of the marginalpropensity to consume (MPC) and the marginal propensity to save (MPS) when determining thesaving rate. Meanwhile, students with low reasoning exhibited fundamental conceptual errors,including incorrect calculation of MPC and misconceptions about the relationship between MPCand saving behavior. These findings highlight the importance of providing differentiated scaffoldingbased on students' reasoning levels, particularly to strengthen conceptual understanding amonglow-level students and mathematical justification skills among medium-level students.